การนำเสนอแนวทางการพัฒนาครูการศึกษานอกระบบและการศึกษาตามอัธยาศัยด้านการจัดกระบวนการเรียนรู้ตามหลักสูตรการศึกษาขั้นพื้นฐานนอกระบบ - ธนิสร เกษมสันต์ ณ อยุธยา (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This descriptive research aims to 1) study problems and needs of non-formal and informal education teachers regarding the learning process management within the Basic Non-formal Education Curriculum; and 2) offer development guidelines for non-formal and informal education teachers with regard to the management of learning process within the Basic Non-formal Education Curriculum. The population in this study consisted of teachers, administrators and students of non-formal and informal education centers across the country. As for the sample group, the researcher used multi-stage sampling to select 350 teachers, administrators and students of non-formal and informal education centers in Bangkok, while purposive sampling was employed to select executive administrators, scholars or experts of the Office of Non-formal and Informal Education Center in Bangkok. The research instruments included a questionnaire, an interview question from concerning problems and needs of non-formal and informal education teachers regarding the learning process management within the Basic Non-formal Education Curriculum, and a focus group discussion. The results were as follows: 1) The problems and needs of non-formal and informal education teachers on the subject of learning process management within the Basic Non-formal Education Curriculum can be divided into 4 aspects: knowledge, skills, attitudes and good characteristics. The problems in these aspects were rated at the moderate level. The knowledge was the main problem with the highest mean score of 3.08, while the attitude was reported the lowest mean score of 2.87. In addition, the needs in these aspects were found at the high level. The needs of knowledge was reported at the highest mean score of 3.65; and the needs of attitude was at the lowest mean score of 3.51. 2) The developed guidelines included four aspects: knowledge, skills, attitudes and good characteristics. Regarding to the knowledge, the teachers should be trained to acquire profound knowledge of the basic subjects and given the opportunities to develop an understanding of the learning process in different fields. In terms of the skills, teachers should be helped to understand how to construct and develop curricula that serve learners’ needs. For example, there should be trainings on techniques in learning management for adults. Concerning the attitudes, teachers should be encouraged to gain a full understanding about their roles and responsibilities as teachers. For instance, teachers should understand and accept individual differences in students. In the good characteristics, the expected characteristics of teachers in each educational institution should be provided. For example, creativity and lifelong learning should be promoted among teachers in order to help them to better manage the learning process of their learners.